2002
DOI: 10.1128/cdli.9.2.485-488.2002
|View full text |Cite
|
Sign up to set email alerts
|

Opsonophagocytosis of Fluorescent Polystyrene Beads Coupled to Neisseria meningitidis Serogroup A, C, Y, or W135 Polysaccharide Correlates with Serum Bactericidal Activity

Abstract: We developed a polysaccharide-specific flow cytometric opsonophagocytic assay (OPA) for the simultaneous measurement of functional antibody to Neisseria meningitidis serogroups A, C, Y, and W135. OPA titers significantly correlated with serum bactericidal assay titers for all serogroups tested (mean r ‫؍‬ 0.96; P < 0.001). OPA could be used in meningococcal vaccine evaluation.Meningococcal disease continues to be a significant cause of morbidity and mortality in the United States and worldwide (3). The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Demonstration of killing of meningococci by opsonophagocytosis (24,25), coupled with the establishment of the OPA as the surrogate of protection for Streptococcus pneumoniae (19), has led to the development of an OPA against meningococci (1,20). Immunization with meningococcal polysaccharide vaccines elicits complement-dependent serum bactericidal and opsonizing antibodies, with both mechanisms operating simultaneously to clear meningococci (7,8,9,26).…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration of killing of meningococci by opsonophagocytosis (24,25), coupled with the establishment of the OPA as the surrogate of protection for Streptococcus pneumoniae (19), has led to the development of an OPA against meningococci (1,20). Immunization with meningococcal polysaccharide vaccines elicits complement-dependent serum bactericidal and opsonizing antibodies, with both mechanisms operating simultaneously to clear meningococci (7,8,9,26).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly for vaccine development, SBA is a ready marker of immunity for preclinical assessment of vaccines and provides a suitable end point in clinical trials. The importance of opsonophagocytic killing as a defense mechanism against the meningococcus has been demonstrated recently, with titers of opsonophagocytosis of beads coated with capsular antigen shown to be significantly correlated with SBA directed against capsular antigens (34). In the present study, we have shown that systemic immunization with two strains of N. lactamica (L13 and Y92-1009) elicits high-level bactericidal activity in mice against N. meningitidis strains, including the serogroup B strain, MC58.…”
Section: Discussionmentioning
confidence: 53%
“…These results are consistent with the conclusions of the 1969 Goldschneider et al studies (10,11) that the presence of serum bactericidal activity is a reliable marker of protection against disease but that the absence of serum bactericidal activity does not necessarily imply susceptibility, since not all recruits who lacked serum bactericidal activity and who became colonized with the epidemic strain developed invasive disease. Although not directly tested in our study, the most likely mechanism responsible for protective activity in the absence of serum bactericidal activity is opsonization (21), which can result from antibody binding to the bacterial surface and activation of C3b deposition without proceeding to bacteriolysis (36). Alternatively, there may be blocking of bactericidal antibodies in vitro, for example, by the presence of non-complement-activating IgA antibodies (14).…”
Section: Discussionmentioning
confidence: 99%